Fatherhood: Comparison Between Divorced Custodial Fathers, Married Fathers, and Divorced Non-Custodial Fathers in Israel. Issue 4 (19th May 2017) - Finzi-Dottan, Ricky; Cohen, Orna
ABSTRACT: Paternal involvement and acceptance were compared among 218 custodial fathers, 222 married fathers, and 105 divorced noncustodial fathers. Findings show that the custodial fathers were more involved with their children, coordinated less with their children's mother, and viewed their children as more difficult than the other fathers. Two regression analyses were conducted. One revealed that greater paternal involvement was predicted by greater self-differentiation, greater sense of having received care from one's own father, and a less avoidant caregiving disposition. The other showed that greater paternal acceptance was predicted by greater self-differentiation, greater sense of having received care from one's own father, and a less anxious caregiving disposition. Finally, the findings show that coparenting, social support, and sense of the child as difficult moderated the associations between the fathers' personal variables and their involvement, but not their acceptance.